Cloud Computing Based Thesis Collaborative Platform to Support Inovation and Development of IT Solution - Andrew Ercole, Bradley; Erzed, Nixon (CV. Publikasi Indonesia, 2024)
Even though a thesis is an important scientific work produced by students in higher education, the innovative ideas and solutions from the thesis often do not receive follow-up or a platform for real implementation. It is estimated that more than 100,000 undergraduate graduates in information technology (IT) each year have the potential to produce innovative IT solutions through their thesis. To overcome these problems, this research proposeoks developing a collaborative thesis platform based on cloud computing. This platform aims to be a forum for students to realise innovative and quality ideas from their theses. The platform will facilitate collaboration between students and parties who need IT solutions and provide incentive income opportunities for the students involved. By leveraging cloud computing, the platform offers quick and easy access to necessary resources without worrying about local server maintenance. It is hoped that this platform can encourage the development of innovative and quality IT solutions by utilizing ideas from the thesis. The platform has the potential to increase IT graduates' contribution to information technology development, open up incentive income opportunities for students, and facilitate student-industry collaboration in producing IT solutions relevant to real needs.